Climate change and Lithuanian roads: impacts, vulnerability and adaptation - Nemaniutė-Guzienė, Jolanta; Kazys, Justas (International Conference “Environmental Engineering”, 2017)
In Lithuania, like in other countries, climate change causes and will cause changes in natural and anthropogenic environment. The entire transport sector will be impacted, influencing the way it plans, designs, constructs and maintains infrastructure in the future. Roads are already sensitive to current climate variability. If today’s extreme weather events become both more frequent and extreme, so too will the level of disruption that they cause. Thus, roads must be adapted to changing climate conditions. The aim is to ensure resilience, to ensure that roads remain open under extreme weather conditions. The easiest and the most effective economically way is to implement adaptation measures for the new or reconstructed roads. But the existing older roads should be adapted also. The steps required to improve and maintain resilience of roads are definition of climate projections, identification of key roads and their vulnerability, identification and research on technologies for adaptation, preparation of methodologies, establishment of field operational trials. The aim of the research is to review Lithuanian roads in the context of climate change and its consequences. Methodology: climate and associated data collection and review, initial prognoses of the change (in short, medium and long term perspective) of meteorological elements, vulnerability assessment of the study area and the roads. Results: initial recommendations for adaptation action planning.